Protocyon troglodytes (Lund) ( Mammalia, Carnivora ) in the late Pleistocene of Rio Grande do Sul and their paleoecological significance - Oliveira, Édison V. (2005)
An incomplete maxilla with P4 and M1, from the late Pleistocene lacustrine sands of the System Barrier III (Santa Vitória Formation), is the first record of Protocyon troglodytes (Lund) for the State of Rio Grande do Sul, Brazil. This material differs from Theriodictis, a closely related genus, in characters of the P4 (protocone more reduced) and M1 (hypocone more reduced, and the inner half mesiodistally narrower and straighter). Differently of southern Brazil living canids such as Chrysocyon brachyurus, Cerdocyon thous and Dusicyon gymnocercus, P. troglodytes developed dental adaptations associated to hypercarnivory in having large paracone on M1, strong reduction of protocone on P4 and reduction and simplification of talonids. In the latest Pleistocene, the climate was colder and grassland landscapes were predominant in southern Brazil, where several potential large and medium-sized ungulate preys were present. Protocyon troglodytes probably preyed on medium-sized grazers or browsers but not on the megafauna, or only on young individuals of this size class.